Multifunctional iron oxide–carbon hybrid microrods. Issue 101 (17th October 2016) - Zhu, Lu; Huang, Weijie; Rinehart, Zachary S.; Tam, Jason; Zhao, Yiping
Abstract : Fe x O y –C microrods with superior dye adsorption and drug loading abilities were obtained by solvothermal synthesis with annealing. Abstract : In this work, iron oxide microrods (MRs) with different crystal phases were successfully fabricated by a facile solvothermal method and sequential annealing processes. It was found that the carbon content remained in the structure when annealing at low temperature (150 °C). The carbon in the MRs contributed to the higher dye adsorption and drug loading capabilities of the MRs. The Fe3 O4 –C sample showed superior adsorption for both a cationic dye (methylene blue) and an anionic dye (methyl orange) with an equilibrium adsorption capability of 11.7 mg g −1 and 20.8 mg g −1, respectively. When applied as a drug carrier for a tissue plasminogen activator, the mass loading ratio of the MRs was as high as 12.9% for chemical loading and 7.8% for physical loading. With the high dye adsorption/drug loading ratio, such magnetic structures show promise for use in water treatment and advanced medical applications.